2015
DOI: 10.1016/j.ijdevneu.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal undernutrition increases the febrile response to lipopolysaccharides in adulthood in male rats

Abstract: It has been reported that prenatal undernutrition affects the development of the peripheral immune system. In this study, the effects of prenatal undernutrition on the febrile response and hypothalamic innate immune system were evaluated in male rats. Pregnant rats were divided into normally nourished (NN) and undernourished groups (UN). The febrile and anorectic responses to lipopolysaccharides (LPS) were evaluated in the offspring of NN and UN dams. The hypothalamic expression levels of pro-inflammatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…Twenty‐four hours later (between 0900 and 1000), the rats' brains were collected by decapitation and stored at −80 ˚C after being snap frozen. Whole hypothalamic explants were dissected from the frozen brains, as described previously (Iwasa et al, 2015a,b,c). Total RNA was isolated using a TRIzol(r) reagent kit (Invitrogen Co., Carlsbad, CA, USA) and an RNeasy(r) mini kit (Qiagen Gmbh, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty‐four hours later (between 0900 and 1000), the rats' brains were collected by decapitation and stored at −80 ˚C after being snap frozen. Whole hypothalamic explants were dissected from the frozen brains, as described previously (Iwasa et al, 2015a,b,c). Total RNA was isolated using a TRIzol(r) reagent kit (Invitrogen Co., Carlsbad, CA, USA) and an RNeasy(r) mini kit (Qiagen Gmbh, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…As noted above, prenatal undernutrition affects some physiological functions after birth and causes various diseases in adulthood (Godfrey and Barker, 2000; Breier et al, 2001; Gluckman and Hanson, 2004). Recently, we have shown that the offspring (male rats) of a food‐restricted dam exhibited increased febrile and anorectic responses to the injection of a moderate dose of LPS in adulthood, suggesting that prenatal undernutrition also affects stress responses in later life (Iwasa et al, 2015). However, it remains unclear whether prenatal undernutrition also affects stress responses under severe stress conditions, such as septic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, infants that are small‐for‐gestational‐age are at increased risk of infection‐induced sepsis during the neonatal period and childhood (Smichen et al, 2000), and IUGR rats exhibit increased innate immunological activity (Equils et al, 2005). Recently, we have reported that prenatally undernourished male rats displayed stronger febrile and anorectic responses to immune stress induced by the injection of a moderate dose of lipopolysaccharides (LPS) in adulthood than prenatally normally nourished rats (Iwasa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that immune stress suppresses some reproductive functions and that the reductions in serum gonadotropin levels caused by increased hypothalamic pro‐inflammatory cytokine activity play pivotal roles in these alterations (Yoo et al, 1997; Watanobe and Hayakawa, 2003; Matsuwaki et al, 2006; Iwasa et al, 2015a). As noted above, in a previous study we showed that prenatal undernutrition alters the febrile response to LPS in adulthood (Iwasa et al, 2015a), indicating that prenatal nutritional status might have long‐term effects on different kinds of physiological functions, as well as metabolic regulation, in adulthood. Similarly, some groups have detected relationships between prenatal undernutrition and immune functions.…”
Section: Discussionmentioning
confidence: 99%